2022
DOI: 10.1145/3555144
|View full text |Cite
|
Sign up to set email alerts
|

'Don't make assumptions about me!': Understanding Children's Perception of Datafication Online

Abstract: Datafication, which is the process in which children's actions online are pervasively recorded, tracked, aggregated, analysed, and exploited by online services in multiple ways that include behavioural engineering, and monetisation, is becoming increasing common in the online world today. However, we know little about how children feel about such practices and how they perceive datafication. Through online interviews with 48 children aged 7-13 from UK schools, we examined how children perceive datafication pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Given this, we use participatory methods, allowing young people to shape the research agenda. We also engaged mixedmethod, using many youth-friendly activities, like hypothetical and 'real' scenarios, which have successfully been used in research around young people and privacy [4,5].…”
Section: A Common Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this, we use participatory methods, allowing young people to shape the research agenda. We also engaged mixedmethod, using many youth-friendly activities, like hypothetical and 'real' scenarios, which have successfully been used in research around young people and privacy [4,5].…”
Section: A Common Research Methodsmentioning
confidence: 99%
“…While there is extensive research exploring children and young people's potentially harmful experiences within the digital context, such as dangerous content, grooming and abuse or risky online behaviors like cyberbullying to excessive 'screentime', there has been a far more limited focus on exploring children and young people's privacy concerns [3]. Previous research has often identified that young people hold unique ideas about privacy [4,5], identifying privacy as a right which they feel is often challenged or threatened, [6] and that there is a gap in research around young people's perspectives around commercial contexts, which is rapidly important in the increasing commercially digital environment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Design exemplars include supporting children's cognitive understanding of key computational concepts through child-friendly ways, such as Lego's Caption Safety [92] and Google's Be Internet Legends [61]; designs that support children to make sense of what happened around their data, such as Cracknell Law's situated cartoon design [80]; designs that help children comprehend the online risks around them, such as stranger danger and online inappropriate content [140]. Meanwhile, a growing body of research has been carried out regarding how to empower children with greater control over their interaction with the digital technologies, such as through having greater autonomy on their online media choices [59,71], and dealing with various kinds of online risks [141,152].…”
Section: Hci Research Around Designing For Children's Autonomy Onlinementioning
confidence: 99%
“…Although development research on children has been emphasising a holistic approach to their autonomy support, little has been understood in terms of the theoretical grounding related to supporting children's digital autonomy: the relationship and transition between children's knowledge acquisition, behaviour change and self-regulations in the context of digital autonomy has not been conclusively discussed [6,32]. Such understandings would provide crucial inputs not only for future development of support for children's digital autonomy, but also the current attention on children's digital literacy development [86,127] and its relationship with children's ability to cope with various online risks, datafication and associated autonomy building skills development [141,151,152].…”
Section: Connecting Autonomy Design Mechanisms To Digital Autonomymentioning
confidence: 99%
“…According to Chubb et al (2022), child-friendly interface design is the deliberate creation and arrangement of digital interfaces, applications, and platforms, carefully considering young users' unique cognitive, emotional, and developmental needs. This design approach prioritizes elements such as intuitive navigation, visually appealing graphics, clear instructions, ageappropriate content, and interactive features that resonate with children's cognitive capacities and preferences (Wang et al, 2023). Child-friendly interface design, characterized by its intentional layout and user-centric features, serves as a gateway through which children first encounter and navigate the digital landscape (Horn, 2018).…”
Section: Child-friendly Interface Design Early Childhood Digital Lite...mentioning
confidence: 99%